Protecting children against exposure to content risks online in Malaysia: lessons from Australia - Daud, Mahyuddin; Abd. Jalil, Juriah (The Faculty of Law, Universiti Teknologi MARA (UiTM), 2016)
Children are the most vulnerable group in any civil society. The rise of digital technology has made them more exposed to threats of content risks online through exposure to illegal and harmful Internet content. To make matters worse, the legal framework regulating the Internet in Malaysia i.e. self-regulation does not mandate service providers to implement technical measures that could help reduce children’s exposure to content risks. Continuous exposure to content risk could lead to dilution of traditional values among younger generation. In order to reduce this outcome, all Internet stakeholders in Malaysia must take Internet regulation more seriously. The first part of this paper argues that content risks are a real threat to children in Malaysia as seen in previous studies. In the second part of this paper, library research and focus group discussions with Malaysian Communications and Multimedia Commission (MCMC), selected Internet service providers in Malaysia and the Communications and Multimedia Content Forum (CMCF) were conducted to analyse regulatory measures practiced in the Malaysian self-regulation framework. Non-censorship policy that does not mandate service providers to classify nor filter prohibited content was found problematic since it had greatly exposed children to content risks. Australian co-regulation was critically examined in the final part of this paper. The scheme has been focusing on protection of children online through classification and filtering measures. Lessons learnt from the Australian jurisdiction could be of reference to Malaysia in its effort to reduce children’s exposure to content risks online.